Terroryzm ekologiczny jako przestępstwo - Szumski, Adrian (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Terrorism belongs to the most serious challenges that contemporary world must face. Terroristic deeds violate the foundations of states and societies, and they are threat for their proper functioning. Simultaneously they coerce the authorities of respective states to create proper legal regulations that will penalize this phenomenon. Very wide definition of terrorism includes also so called ecological terrorism. The aim of this article is to answer the question about the place of ecological terrorism among the deeds penalized by the Polish penal code. It is important, because not all unlawful deeds that, in common language, are called “ecological terrorism” may be considered as terrorist acts in the light of the Polish penal law. Designation of adeed as one of aterrorist nature brings also important consequences from the legal point of view. The analysis of legal regulations led me to the conclusion that admittedly the Polish penal law does not reference directly to the crime of “ecoterrorism” but binding legal regulations which concern crimes of terroristic nature may be, in some scope, aground for criminal responsibility. Ialso concluded that these regulations seem to be proper, and there is no need to formulate aseparate definition of ecological terrorism in the Polish penal law, however some utterances included in Polish regulations may cause certain doubts. My conclusion is also that the regulations concerned the financing of crimes of aterroristic nature shall be clarified.
Keywords: terroryzm ekologiczny; polski kodeks karny; przestępstwo